2006
DOI: 10.1002/cm.20132
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined hypergravity and microgrooved surface topography on the behaviour of fibroblasts

Abstract: This study evaluated in vitro the differences in morphological behaviour between fibroblast cultured on smooth and micro-grooved substrata (groove depth: 1 mum, width: 1, 2, 5, 10 microm), which undergo artificial hypergravity by centrifugation (10, 24 and 50 g; or 1 g control). The aim of the study was to clarify which of these parameters was more important to determine cell behaviour. Morphological characteristics were investigated using scanning electron microscopy and fluorescence microscopy in order to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…However, cells cultured on wider microgrooves of either 5 μm or 10 μm in width attached to the substrate just the same as on smooth surfaces, and there was no acceleration of calcification. Loesberg et al (9,10) used the same size microgrooves as Matsuzaka et al (11) and suggested that cell differentiation was accelerated on microgrooves of 1 μm to 2 μm in width, because cells were suspended in the groove as a cellular bridge and exposed receptors existing on the cell membrane, making it easier to get molecular signals such as dexamethasone into the culture medium and cause (or induce) the cells to differentiate into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells cultured on wider microgrooves of either 5 μm or 10 μm in width attached to the substrate just the same as on smooth surfaces, and there was no acceleration of calcification. Loesberg et al (9,10) used the same size microgrooves as Matsuzaka et al (11) and suggested that cell differentiation was accelerated on microgrooves of 1 μm to 2 μm in width, because cells were suspended in the groove as a cellular bridge and exposed receptors existing on the cell membrane, making it easier to get molecular signals such as dexamethasone into the culture medium and cause (or induce) the cells to differentiate into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Centrifuges are applied in various disciplines mainly in material and particle technology like for separation (Sahuquillo et al, 1999;Kuang et al, 2015), for nanomaterials classification (Wohlleben, 2012), casting (Huisman et al, 1994;Liu and Barnett, 2002;Dikel et al, 2005;Velhinho and Rocha, 2011), combustion (Merzhanov, 1995), but also in areas like geology (Gopal Madabhushi, 2004;Costa et al, 2016), life sciences in plants (Musgrave et al, 2009;Herranz et al, 2013;Hoson and Wakabayashi, 2015), single cells (Loesberg et al, 2006;Tavakolinejad et al, 2015), animals (van Loon, 2001;van Loon et al, 2005;Tateishi et al, 2015) and humans (Akima et al, 2005;van Loon et al, 2012;Goswami et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the aforementioned studies have focused on the critical role of cytoskeletal components, actin microfilaments and microtubules in cell alignment (Oakley et al 1997;Wojciakstothard et al 1995). Both mechanical loading and microgrooved surface topographies promote cytoskeletal reorganization and affect the behavior of fibroblast cells (Loesberg et al 2005(Loesberg et al , 2006. Cytoskeletal proteins play an important role in tissue engineering by mediating the cellular response to different substrates.…”
mentioning
confidence: 99%